Tribological Analysis of Fused Filament Fabrication PETG Parts Coated with IGUS - Moises Batista; Delia Tenorio; Irene Del Sol; Juan Manuel Vazquez-Martinez (Applied Sciences, 2024)
This paper studied the tribological behaviour of parts manufactured using fused filament fabrication (FFF) technology with PETG (polyethylene terephthalate glycol) coated with IGUS tribological filaments. The research focuses on analysing how these multi-material parts behave under different loads. The objective of this study is to evaluate the wear resistance and friction coefficient of parts coated with different thicknesses of IGUS material. The methodology employs pin-on-disc (PoD) tribological tests to measure behaviour under various load conditions and coating thicknesses. The results indicate that increasing the coating thickness improves surface stability and reduces roughness, although it does not significantly affect the average friction coefficient. This research concludes that coating thickness has a moderate impact on surface quality and that the applied load significantly influences the depth and width of the wear groove. This contribution is valuable for the field of additive manufacturing as it provides a better understanding of how to optimise the tribological properties of parts manufactured using FFF, which is crucial for industrial applications where wear and friction are critical factors. The practical application includes the potential improvement of components in the automotive and aerospace industries.